EVALUATION OF THE QUALITY OF THE LEARNING PROCESS THROUGH ACADEMIC SUPERVISION IN MADRASAH IBTIDAIYAH - Meisuri Meisuri; Nurul Hidayah (STKIP Pesisir Selatan, 2026)
This study aims to describe the implementation of academic supervision by madrasah principals in the planning, implementation, evaluation, and follow-up stages; and to identify the obstacles faced by teachers in the academic supervision process at an elementary madrasah. Methods: The study used a descriptive qualitative approach with a case study design in an elementary madrasah in Bandar Lampung City. Data were collected through classroom observations, semi-structured interviews with madrasah principals, teachers, and supervisors, as well as studies of planning documents and supervision instruments, then analyzed using the interactive model of Miles and Huberman which includes data reduction, data presentation, and conclusion drawing. Result: The results of the study indicate that academic supervision has been planned in a scheduled manner, but its implementation in the field is still administrative-formalistic, classroom observations are short and rarely followed by in-depth reflective coaching, and follow-up of supervision results has not been systematically documented. The quality of the learning process in the planning aspect is quite good, but in the implementation and assessment aspects of authentic learning still varies between teachers. The main obstacles faced by teachers include the principal's limited time, the high administrative burden of class teachers on thematic learning, gaps in understanding of supervision instruments, and a tendency for unnatural teaching performance during supervision.